A strong reconstruction option for tissue loss on hand and wrist due to firearm injury in the Syrian war: Reverse posterior interosseous flap. Issue 32 (13th August 2021) - Ucak, Murat
Abstract : Abstract: All of the injuries were the open injuries with bone or tendon structures in the hand and wrist region as a result of the firearm injury (FI) in the Syria. In the study, we assessed the outcomes of the posterior interosseous flap (PIF) on hand and wrist that we used for the Syrian injured people including civilians and soldiers in this War. PIF was applied to 77 patients who composed of 43 female and 34 male that all patients were evaluated for tissue loss resulting from gunshot wounds and injured in the War between 2014 and 2020 years with tissue loss in hand and wrist as a result of FI. The flap survival rate was 100% for all the patients. The dimensions of flaps ranged from 4.1 cm × 2.2 cm to 9cm × 5.4 cm with 0.51 ± 0.12 cm thickness. The mean pedicle length was 6.33 ± 1.08 cm. The surgery for PIF took 68.8 ± 22.1 minutes, while blood loss was 60 ± 24 mL. We observed no palsy conditions including the posterior interosseous nerve. The donor sites were treated by primary intention in the patients. We found the superiority of PIF with the postoperative follow-up comfort, ease of fracture healing, easy and fast, easy-to-apply method and no second additional session requirement in FI patients. We did not detect flap necrosis in any patient or observe a flap-related complication. As a result of the present study, it strongly supports the thesis that PIF is the best option in these cases.